The Effectiveness of a Training Program in Improving Mathematics Teachers’ Professional Efficacy in Including Students with Learning Disabilities in Mainstream Classrooms - Abu Alrub, Salwa Tawfeq; Alzoabi, Ali; Jawarneh, Tariq (Dirasat: Educational Sciences, 2020)
This study aimed to reveal the effectiveness of the training program in improving Mathematics Teachers’ Professional efficacy in including students with learning disabilities in mainstream classrooms. The study sample consisted of (20) mathematics teachers chosen possessively from BANI KANANA educational directorate. The sample was divided into two identical groups: control group and an experimental group. The experimental group was subjected to a training program relating to inclusion. Data was collected by using mathematics teacher efficacy scale. The results showed that there was a statistically significant difference between the two groups in favor of the experimental group, which means that the program helped to introduce teachers to students with math learning disabilities, their characteristics, the methods of diagnosing them. In addition, the results revealed the program was conducive with regard to raising the efficiency of teachers and their desire to use alternative instructional strategies, to control student behavior and activating the participation of students with learning disabilities in mainstream classrooms.